The UK joint specialist societies guideline on the diagnosis and management of acute meningitis and meningococcal sepsis in immunocompetent adults. Issue 4 (April 2016) - McGill, F.; Heyderman, R.S.; Michael, B.D.; Defres, S.; Beeching, N.J.; Borrow, R.; Glennie, L.; Gaillemin, O.; Wyncoll, D.; Kaczmarski, E.; Nadel, S.; Thwaites, G.; et al.
Summary: Bacterial meningitis and meningococcal sepsis are rare conditions with high case fatality rates. Early recognition and prompt treatment saves lives. In 1999 the British Infection Society produced a consensus statement for the management of immunocompetent adults with meningitis and meningococcal sepsis. Since 1999 there have been many changes. We therefore set out to produce revised guidelines which provide a standardised evidence-based approach to the management of acute community acquired meningitis and meningococcal sepsis in adults. A working party consisting of infectious diseases physicians, neurologists, acute physicians, intensivists, microbiologists, public health experts and patient group representatives was formed. Key questions were identified and the literature reviewed. All recommendations were graded and agreed upon by the working party. The guidelines, which for the first time include viral meningitis, are written in accordance with the AGREE 2 tool and recommendations graded according to the GRADE system. Main changes from the original statement include the indications for pre-hospital antibiotics, timing of the lumbar puncture and the indications for neuroimaging. The list of investigations has been updated and more emphasis is placed on molecular diagnosis. Approaches to both antibiotic and steroid therapy have been revised. Several recommendations have been given regarding the follow-up of patients. Highlights: Up-to-date recommendations for managing adults with meningitis and meningococcal sepsis in the UK. Includes viral meningitis Includes audit tool Includes algorithm